Fast 3D reconstruction based on UAV image. (December 2020) - Pang, Qiaoyu; Gui, Jianjun; Li, Jing; Deng, Baosong
Abstract: 3D reconstruction for outdoor large environment, especially with high efficiency and robustness, has triggered increasing attention in both civilian and military scenario. This paper proposes a rapid method to perform 3D reconstruction using openMP multithreading strategy. The GPS information will be adopted to determine the adjacent relationship between images. The map will be processed through mesh blocks to save the computational time, and will be finally optimized by the mesh dissecting algorithm to remove holes. The experimental results show that the processing speed has been increased as five times faster than the methods based on openMVG and openMVS with better reconstruction outputs.